2006
DOI: 10.1016/j.tcs.2006.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Enumeration of subtrees of trees

Abstract: Let $T$ be a weighted tree. The weight of a subtree $T_1$ of $T$ is defined as the product of weights of vertices and edges of $T_1$. We obtain a linear-time algorithm to count the sum of weights of subtrees of $T$. As applications, we characterize the tree with the diameter at least $d$, which has the maximum number of subtrees, and we characterize the tree with the maximum degree at least $\Delta$, which has the minimum number of subtrees.Comment: 20 pages, 11 figure

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(56 citation statements)
references
References 3 publications
0
56
0
Order By: Relevance
“…The number of leaf-containing subtrees of a binary tree provides a bound on the number of acceptable residue configurations, needed in the study of the complexity of a multiple parsimony alignment in phylogeny [14]. Much work has been done on this topic, including but not limited to, that of Szekely and Wang [41][42][43], Kirk [44], Czabarka [45], Vince [46], Zhang and Zhang [47,48], Yan and Yeh [49], Li [50], Jamison [51], Haslegrave [52], Andriantiana [53]. In particular, a linear-time algorithm to evaluate the sum of weights of subtrees of T through "generating functions" was provided in [49].…”
Section: Introductionmentioning
confidence: 99%
“…The number of leaf-containing subtrees of a binary tree provides a bound on the number of acceptable residue configurations, needed in the study of the complexity of a multiple parsimony alignment in phylogeny [14]. Much work has been done on this topic, including but not limited to, that of Szekely and Wang [41][42][43], Kirk [44], Czabarka [45], Vince [46], Zhang and Zhang [47,48], Yan and Yeh [49], Li [50], Jamison [51], Haslegrave [52], Andriantiana [53]. In particular, a linear-time algorithm to evaluate the sum of weights of subtrees of T through "generating functions" was provided in [49].…”
Section: Introductionmentioning
confidence: 99%
“…We showed, however, that for the class of cographs the g-convex sets can be enumerated in linear time. It was observed, using the results from [26], that the number g-convex sets of trees can also be enumerated in linear time.…”
Section: Resultsmentioning
confidence: 99%
“…In [26] it was shown that the number of subtrees of a tree can be determined in linear time. Since the subtrees of a tree are precisely the g-convex sets of a tree, this result shows that the number of g-convex sets of a tree can be determined in linear time.…”
Section: Counting G -Convex Setsmentioning
confidence: 99%
“…This "subtree polynomial" was already considered by Jamison himself in [5]. More recently, Yan and Yeh [18] studied a weighted version, and Martin et al [9] considered a bivariate generalisation involving the number of leaves.…”
Section: Many Other Ofmentioning
confidence: 95%